THE UTILIZATION OF MADRASAH E-LEARNING IN THE IMPLEMENTATION OF DISTANCE LEARNING IN PANDEMIC PERIOD IN MA USB FILIAL MAN BATAM - Jemmy Muhammad (JURNAL TIKAR, 2022)
Coronaviruse Disease 2019 (Covid-19) has an impact on the teaching and learning process that must be done remotely, to protect the safety and health of students from the threat of Covid-19. MA USB FILIAL MAN BATAM as one of the institutions under the Ministry of Religion has taken advantage of the Ministry of Religion's distance learning application, namely Madrasah E-learning. This study aims to describe the use of distance learning using Madrasah E-Learning for MA USB FILIAL MAN BATAM students. This research uses quantitative research methods with descriptive quantitative design (survey). The data collection technique used an online questionnaire using Microsoft Form. The results showed that the Madrasah E-learning application proved to be useful as a learning technique during the 2019 Coronavirus Disease Pandemic (Covid-19). This can be seen from the results of the questionnaire given to respondents on average showing that Madrasah E-Learning can be the main means and choice for the implementation of teaching and learning activities for MA USB FILIAL MAN BATAM students during the Coronaviruse Disease 2019 (Covid-19) pandemic when this.